Comparison of the enzymatic depolymerization of polyethylene terephthalate and AkestraTM using Humicola insolens cutinase - Aristizábal-Lanza, Lucía; Mankar, Smita V.; Tullberg, Cecilia; Zhang, Baozhong; Linares-Pastén, Javier A. (Frontiers in Chemical Engineering, 2022)
The enzymatic depolymerization of synthetic polyesters has become of great interest in recycling plastics. Most of the research in this area focuses on the depolymerization of polyethylene terephthalate (PET) due to its widespread use in various applications. However, the enzymatic activity on other commercial polyesters is less frequently investigated. Therefore, AkestraTM attracted our attention, which is a copolymer derived from PET with a partially biobased spirocyclic acetal structure. In this study, the activity of Humicola insolens cutinase (HiCut) on PET and AkestraTM films and powder was investigated. HiCut showed higher depolymerization activity on amorphous PET films than on Akestra™ films. However, an outstanding performance was achieved on AkestraTM powder, reaching 38% depolymerization in 235h, while only 12% for PET powder. These results are consistent with the dependence of the enzymes on the crystallinity of the polymer since Akestra™ is amorphous while the PET powder has 14% crystallinity. On the other hand, HiCut docking studies and molecular dynamic simulations (MD) suggested that the PET-derived mono (hydroxyethyl)terephthalate dimer (MHET)2 is a hydrolyzable ligand, producing terephthalic acid (TPA), while the Akestra™-derived TPA-spiroglycol ester is not, which is consistent with the depolymerization products determined experimentally. MD studies also suggest ligand-induced local conformational changes in the active site.